Normal pace walking is beneficial to young participants' executive abilities - J. N. Zhang; L. S. Xiang; Y. Shi; F. Xie; Y. Wang; Y. Zhang (BMC, 2022)
Abstract Background Exercise can improve cognitive function. The impact of acute exercise on cognition is related to exercise intensity. This study aimed to explore whether normal walking had a beneficial effect on cognition. Methods Compared with standing still, thirty healthy young men walked on a treadmill at a normal pace, and completed the Stroop test. Near-infrared spectroscopy was used to monitor the hemodynamic changes of the prefrontal cortex during the entire experiment. Results Studies showed that normal walking did not stimulate higher average cerebral oxygen in the PFC, but the peak cerebral oxygen in cognitive tests during walking was higher (Stroop Word: 2.56 ± 0.43 and 3.80 ± 0.50, P < 0.01, Stroop Color: 2.50 ± 0.37 and 3.66 ± 0.59, P < 0.05, Stroop Color-Word: 4.13 ± 0.55 and 5.25 ± 0.66, P < 0.01, respectively), and better results were achieved in the Stroop Color-Word test, which was reflected in faster reaction times (49.18 ± 1.68 s, 56.92 ± 2.29 s, respectively, P < 0.001) and higher accuracies (46.19 ± 0.69, 44.15 ± 0.91, respectively, P = 0.018). Conclusion For healthy young people, even a normal walk is therefore good for cognition.